2020
DOI: 10.1213/ane.0000000000004988
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Applied to Registry Data: Development of a Patient-Specific Prediction Model for Blood Transfusion Requirements During Craniofacial Surgery Using the Pediatric Craniofacial Perioperative Registry Dataset

Abstract: Background: Craniosynostosis is the premature fusion of ≥1 cranial sutures and often requires surgical intervention. Surgery may involve extensive osteotomies, which can lead to substantial blood loss. Currently, there are no consensus recommendations for guiding blood conservation or transfusion in this patient population. The aim of this study is to develop a machine-learning model to predict blood product transfusion requirements for individual pediatric patients undergoing craniofacial surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The included studies were from sixteen journals, with only 2 articles each were published in Clinical Orthopaedics and Related Research [ 24 , 25 ] and Medicina [ 26 , 27 ]. Thirty-three percent of these studies (7/18) were conducted in the United States [ 24 , 25 , 28 32 ], with 17% (3) in China [ 26 , 33 , 34 ]. Study designs included cohort study (83%; 15) and cross-sectional database study (17%; 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were from sixteen journals, with only 2 articles each were published in Clinical Orthopaedics and Related Research [ 24 , 25 ] and Medicina [ 26 , 27 ]. Thirty-three percent of these studies (7/18) were conducted in the United States [ 24 , 25 , 28 32 ], with 17% (3) in China [ 26 , 33 , 34 ]. Study designs included cohort study (83%; 15) and cross-sectional database study (17%; 3).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 58 to 10534 [ 26 , 36 ]. Two studies [ 28 , 38 ] did not provide data on the age and sex of participants.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] Models predicting which patients require therapy, and the effect of treatment, have more recently been reported as well as those predicting adverse events. 15,16 Perhaps the best example is intraoperative hypotension, a common adverse event with a clear relationship to multiple organ system injuries. 17 The Hypotension Prediction Index (HPI) was one of the first models created that targeted hypotension and the only one demonstrated to reduce hypotension exposure when incorporated into care delivery, compared to care without it.…”
Section: Machine Learning (Ml) and Predictive Analyticsmentioning
confidence: 99%
“…However, this strategy often ignores other potential preoperative indicators and may lead to one-sided and inappropriate transfusion. Recent studies have identified other risk factors including BMI, age, blood pressure, or use of medications, and showed that Hb might not be the most critical risk factor in postoperative RBC transfusion (10,11). Therefore, more modifiable factors should be considered before the RBC transfusion decision is made.…”
Section: Introductionmentioning
confidence: 99%